The Effectiveness of Applying Choral Reading Method on The Students’ Reading Comprehension in Recount Text - Axelina, Mersi; Setiawan, Agus (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The objective of this research aims to find out whether a choral reading method effective or not in teaching reading comprehension at eleventh grade in SMA Negeri 2 Kabupaten Sorong. Relate to the objective of the research use pre-experimental quantitative research design. The design of this research is one group pretest- post-test. The population of this research is eleventh grade students divide eight classes that are XI IPA 1, XI IPA 2, XI IPA 3, XI IPA 4 and the total them are 137 students. Based on purposive sampling, the researcher chose XI IPA 2 and which total are 31 students. To collect of the data, the researcher used 20 items multiple choice for pretest and post-test. In analyse the data, the researcher used SPSS 20 program to calculation the data. The result finding of the research showed that the result of N-gain is (20.27) or (21%) the categorize is not effective, it means that H0 is accept and Ha is rejected. The null hypothesis (H0) accept is not effective in teaching reading comprehension using choral reading method between pretest and post-test. but if there seen from the mean score from the pretest is (42,4194) improve on post-test (54,3548). It can be concluded that choral reading method in teaching reading comprehension are not effective in teaching reading.